PROVERBS EMPLOYED IN THE POETRY OF BOBUR BOBOMUROD (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Our people expressed their conclusions and philosophical reflections from life experience through proverbs. Folk proverbs have lived for centuries as examples of the art of words, artistically expressing the life experience of the Uzbek people. Folk proverbs have been incorporated into literary works by poets and writers for a thousand years and have taken their place in the art of words as an example of folklore. In this article, an opinion is expressed about the expression of proverbs, one of the stylistic devices that occupies an important place in the poetry of Babur Babamurad.